Chlorogenic acid alleviates cadmium-induced neuronal injury in chicken cerebral cortex by inhibiting incomplete autophagy mediated by AMPK-ULK1 pathway - Li Wang; Chaofan Zhang; Muhammad Azhar Memon; Qianting Shi; Le Lu; Xishuai Tong; Yonggang Ma; Hui Zou; Jianhong Gu; Xuezhong Liu; Jianchun Bian; Zongping Liu; et al. (Poultry Science)
Cadmium (Cd) is an environmental pollutant that has neurotoxic properties, which poses serious threats to human health and the development of poultry farming. Chlorogenic acid (CGA) is a dietary polyphenol exhibit various biological activities such as antioxidant, anti-inflammatory, and autophagy regulation. In addition, CGA can penetrate the blood-brain barrier and exert neuroprotective effects. This study explored the mechanism of CGA in alleviating Cd-induced cerebral cortical neuron injury in chickens. The results showed that in vivo, CGA reduced the Cd level and alleviated Cd-induced histopathological and ultrastructural damages in the chicken cerebral cortex. Further research has found that CGA alleviated Cd-induced incomplete autophagy and activation of the AMPK-ULK1 pathway. In vitro, AMPK inhibitors (Compound C) could alleviate Cd-induced incomplete autophagy in chicken cerebral cortical neurons. In addition, CGA alleviated the decreased viability, incomplete autophagy, and activation of the AMPK-ULK1 pathway induced by Cd in chicken cerebral cortical neurons. In summary, CGA can alleviate Cd-induced cerebral cortical neuron injury in chickens, which is related to CGA alleviating Cd-induced incomplete autophagy by inhibiting the AMPK-ULK1 pathway.